2008
DOI: 10.1038/sj.cgt.7701116
|View full text |Cite
|
Sign up to set email alerts
|

Urocanic acid-modified chitosan-mediated PTEN delivery via aerosol suppressed lung tumorigenesis in K-rasLA1 mice

Abstract: The low efficiency of conventional therapies in achieving long-term survival of lung cancer patients calls for development of novel options. Revisiting of aerosol gene delivery may provide an alternative for safe and effective treatment for lung cancer. In this study, imidazole ring-containing urocanic acid-modified chitosan (UAC) designed in the previous study was used as a gene carrier. The potential effects of phosphatase and tensin homolog deleted on chromosome 10 (PTEN) on Akt-related signals and cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Our results are supported by a recent report indicating that redundantly activated Akt could contribute to carcinogenesis in the lungs (50). Also, PTEN inactivation could accelerate K-ras-initiated lung tumorigenesis (51), and K-ras mutation-induced lung tumorigenesis could be suppressed by PTEN gene transfection (52). Moreover, CTMP acts as a negative regulator by suppressing Akt activity (53).…”
Section: Discussionsupporting
confidence: 78%
“…Our results are supported by a recent report indicating that redundantly activated Akt could contribute to carcinogenesis in the lungs (50). Also, PTEN inactivation could accelerate K-ras-initiated lung tumorigenesis (51), and K-ras mutation-induced lung tumorigenesis could be suppressed by PTEN gene transfection (52). Moreover, CTMP acts as a negative regulator by suppressing Akt activity (53).…”
Section: Discussionsupporting
confidence: 78%
“…RNA concentration and integrity were determined by measuring the absorbance at 260 nm and by electrophoresis on a 1% agarose gel. For reverse transcription (RT)-PCR, 5 mg of total RNA was reverse transcribed using SUPERSCRIPT RT (Invitrogen) and an oligo (dT) [12][13][14][15][16][17][18] primer (Invitrogen). Real-time RT-PCR was performed in an iCycler detection system (Bio-Rad, Hercules, CA).…”
Section: Evaluation Of Tumor Burdenmentioning
confidence: 99%
“…RNA concentration and integrity were determined by measuring the absorbance at 260 nm and by electrophoresis on 1% agarose gel. For RT-PCR, 5 mg of total RNA was reverse transcribed using SUPERSCRIPT RT (Invitrogen) and oligo (dT) [12][13][14][15][16][17][18] 48 The primer sequences designed for amplification of a b-actin cDNA fragment (541 bp) were 5 0 -GTGGGGCGCCCCAGGCACCA-3 0 and 5 0 -GTCCT TAATGTCACGCACGATTTC-3 0 . Amplification was performed according to Laux et al 49 PCR products were analyzed by electrophoresis on a 0.8% agarose gel and visualized by ethidium bromide (Anco and Rhenium Industries Ltd, Jerusalem, Israel).…”
Section: Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that UAC/PCD4 complexes suppressed tumor angiogenesis, facilitated apoptosis, and inhibited pathways important for cell proliferation, compared with vector control. In addition, they delivered UAC/phosphatase and tensin homolog deleted on chromosome 10 (PTEN) complexes into a K-ras lung cancer mouse model through an aerosol route [61]. UAC/PTEN complexes were found to significantly suppress lung tumors by nuclear complex formation between PTEN and p53 through Akt-related signal pathways as well as cell cycle arrest.…”
Section: Imidazolementioning
confidence: 99%